A new method for ECG recording in the prone position. (14th October 2021) - Cobos Gil, M A; Diz, J; Islas, F
Abstract: Introduction: Prone ventilation is frequently used in critical patients. ECG is usually recorded transposing the precordial positions to the back (Fig. 1A). The resultant precordial leads are unpredictably different from the supine ECG and difficult to interpret. According to the dipole theory and the concept of mirror image electrocardiogram, each precordial point has an antipodal area where a mirror precordial lead can be recorded. Fig. 1B shows the location of the antipodal areas for the precordial points Purpose: Based on this theoretical background we propose to use these antipodal areas to record inverted precordial leads (mirror leads M1 – M6) with diagnostic and monitoring potential. Patients and methods: We have placed the precordial electrodes in the corresponding antipodal area for each precordial point (Fig. 1B) and we have recorded prone ECG in 20 subjects (10 healthy volunteers, 10 cardiac patients) The resultant ECGs (leads M1-M6) were compared with the standard supine ECGs (v1-V6). Results: Mirror leads show low amplitude (especially V2-V4) compared to standard precordials, but are qualitatively quite similar (but inverted) to the supine precordial leads (Fig. 2). Conclusion: We proposed a new method to obtain ECGs in prone patients. The resultant precordial leads are comparable to the standard precordial leads. Funding Acknowledgement: Type of funding sources: None.